Upregulation of the microRNA rno-miR-146b-5p may be involved in the development of intestinal injury through inhibition of Kruppel-like factor 4 in intestinal sepsis. Issue 1 (1st January 2020) - Tong, Li; Tang, Chaoxia; Cai, Changjie; Guan, Xiangdong
ABSTRACT: Regulatory mechanisms of microRNAs (miRNAs) in the development of intestinal sepsis are unclear. This study investigated the role of rno-miR-146b-5p in sepsis-induced intestinal injury. A rat sepsis model was created using the cecal ligation and puncture method. The expression profiles of miRNA and mRNA in sepsis rats were examined using miRNA and mRNA sequencing; rno-miR-146b was selected for further investigation. The mimics and inhibitors of rno-miR-146b-5p were transfected into IEC-6 cells and then with or without lipopolysaccharide (LPS) treatment, and the expressions of Kruppel-like factor 4 (Klf4) and Cyclin D2 (Ccnd2) were assessed by quantitative real-time transcriptase-polymerase chain reaction (qRT-PCR) and western blotting. Next, cell counting kit-8 assay was used to detect cell viability, and scratch wound healing assay was used to assess cell migration. In sepsis rat model, crypt cell proliferation was inhibited and crypt cell apoptosis was increased. Compared with the sham control, results of miRNA and mRNA sequencing showed that there were 17 miRNAs and 1617 mRNAs that were upregulated and 123 miRNAs and 1917 mRNAs that were downregulated in the sepsis model group. The network diagrams and qRT-PCR validation indicated that rno-miR-146b-5p may inhibit the expression of Klf4. By adjusting the expression of rno-miR-146b-5p in IEC-6 cells with or without LPS treatment, we found that increased expression of rno-miR-146b-5p inhibited cell proliferation and migration and inhibited the expression of Ccnd2. rno-miR-146b-5p may play a vital role in the development of sepsis intestinal injury through targeting Klf4 expression and affecting promoter activity of Ccnd2.